2021
DOI: 10.3390/polym13020249
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Investigation of Thiol-Functionalized Cellulose Nanofibrils as a Chronic Wound Environment Modulator

Abstract: There is currently a huge need for new, improved therapeutic approaches for the treatment of chronic wounds. One promising strategy is to develop wound dressings capable of modulating the chronic wound environment (e.g., by controlling the high levels of reactive oxygen species (ROS) and proteases). Here, we selected the thiol-containing amino acid cysteine to endow wood-derived cellulose nanofibrils (CNF) with bioactivity toward the modulation of ROS levels and protease activity. Cysteine was covalently incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In general, aerogels are solid lightweight materials with extremely low density in between 0.001 and 0.2 g/cm 3 , with over 90% porosity with the most prevalent pore diameter of 2-50 nm and with tunable mechanical and chemical properties (Zaman et al, 2020). Concerning the drug delivery and biomedical approaches, aerogels can be utilized for example for controlled drug release, to provide scaffolds for cell colonization, or wound healing (Blasi-Romero et al, 2021;Grenier et al, 2019;Nagy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In general, aerogels are solid lightweight materials with extremely low density in between 0.001 and 0.2 g/cm 3 , with over 90% porosity with the most prevalent pore diameter of 2-50 nm and with tunable mechanical and chemical properties (Zaman et al, 2020). Concerning the drug delivery and biomedical approaches, aerogels can be utilized for example for controlled drug release, to provide scaffolds for cell colonization, or wound healing (Blasi-Romero et al, 2021;Grenier et al, 2019;Nagy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Blasi‐Romero and others prepared cysteine‐conjugated cellulose nanofibrils; they reported that collagenase activity was reduced in a dose‐dependent manner, primarily through inactivation rather than sequestration from protease solution. [ 163 ] This effect was assigned to the modification with thiol groups.…”
Section: Controlling the Protease Expression And Activitymentioning
confidence: 99%
“…The findings of this research underscore the potential of cysteine-modified cellulose nanofibrils as a promising material for the development of bioactive wound dressings, particularly for the treatment of chronic wounds. [175] Xu et al synthesized a hydrogel through the reaction between sodium alginate and cysteine methyl ester, leading to the formation of thiolated alginate (SA-SH). The thiolated alginate rapidly underwent in situ gelation (SA-SS-SA) by covalent bonding within a short span of 20 seconds, resulting in a highly hydrated hydrogel structure.…”
Section: Applications Of Thiolated Poly-and Oligosaccharidesmentioning
confidence: 99%
“…Moreover, the strong intermolecular interactions between thiolated polymers and blood cells, resulting from the electrostatic attraction between cationic polymers (positively charged) and negatively charged blood cells, contribute to their high hemostatic properties. [ 35,175 ] The mechanism underlying the effectiveness of hydrogels as wound dressings can be attributed to their unique properties. Specifically, hydrogels possess the capacity to absorb and retain wound exudates, thereby creating a conducive environment for critical biological events such as fibroblast proliferation and keratinocyte migration.…”
Section: Applications Of Thiolated Poly‐ and Oligosaccharidesmentioning
confidence: 99%